The influence of sensorimotor experience on beauty evaluation of preschool children - Ardizzi, Martina; Ferroni, Francesca; Manini, Aurora; Giudici, Claudia; Maccaferri, Elena; Uccelli, Stefano; Umiltà, Maria Alessandra (Frontiers in Human Neuroscience, 2023)
Nowadays there is a broad consensus on the role of multimodality in the construction of an embodied aesthetic experience in adults, whereas little is known about the relationship between sensorimotor and aesthetic experience during development. To fill this gap, the present study investigated whether sensorimotor experience with sculpting natural materials (i.e., clay or sand) influences beauty judgments offered to abstract artefacts made by the same materials. Five years old children (n.47) were asked to rate tactile (How smooth is it?), visual (How dark is it?) and beauty (How much do you like it?) proprieties of two artefacts using a visual-analogue measurement-tool ad-hoc developed to fit children’s cognitive skills. Participants rated the artefacts before and after a free-hands manipulation with only one of the two sculpting materials, either sand or clay. Results showed that the greater the sensorimotor interaction experienced with the artefacts, the higher the increment of beauty rating offered to the artefacts made by the same material previously manipulated. No modulations were found for tactile and visual ratings. These results demonstrate that, even in pre-school children, aesthetic experience is specifically linked to its sensorimotor component, supporting, from a developmental perspective, the definition of aesthetic experience as intrinsically rooted on beholders’ bodily experience.